INTEGRASI KETEL UAP DAN TUNGKU HEMAT ENERGI PADA AGRO-INDUSTRI TAHU UNTUK MENINGKATKAN AKSES PANGAN RUMAH TANGGA INDUSTRIALIS - Tajidan, Tajidan; Ibrahim, Ibrahim; Nursan, Muhammad (JURNAL AGRIMANSION, 2025)
This study aims to examine the impact of the integration between steam boilers and energy-efficient furnaces in the agro-industry of tofu on the savings in the use of husk fuel and its implications of increasing food access for industrial households. This innovation is driven by the need for energy efficiency, fuel savings, and increased access to food. The research was carried out in Puyung Village, Jonggat District, Central Lombok Regency. The sample unit consists of 30 business units, consisting of 15 business units that use steam boilers and 15 business units that do not use steam boilers. Of the 30 sample units, there are 10 business units that use energy-efficient furnaces and 20 business units that use non-energy-efficient furnaces. The analysis was carried out using cross tables, graphs, and multiple linear regression analysis. The dependent variable (Y) in this study is the cost of husk fuel per kilogram of control raw materials, while the first independent variable is steaming boiler technology (X1) and the second independent variable is energy-efficient furnace (X2). The results of the study showed that the use of steam boilers had a significant effect, while the use of energy-efficient furnaces had a significant effect on the cost savings of husk fuel. The use of energy-efficient furnaces can reduce the cost of husk fuel, in turn increasing access to food for industrialized households